Claudin-related intestinal diseases. (June 2015) - Barmeyer, Christian; Schulzke, Jörg D.; Fromm, Michael
Abstract: With up to 200 m 2 the human intestine is the organ with the largest absorptive surface of the body. It is lined by a single layer of epithelial cells that separates the host from the environment. The intestinal epithelium provides both, selective absorption of nutrients, ions, and water but also a highly effective barrier function which includes the first line of defense against environmental antigens. The paracellular part of this barrier function is provided by tight junction (TJ) proteins, especially the large family of claudins. Changes in abundance or molecular structure of claudins can generally result in three typical effects, (i) decreased absorptive passage, (ii) increased secretory passage of small solutes and water causing leak flux diarrhea and (iii) increased absorptive passage of macromolecules which may induce inflammatory processes. Several intestinal diseases are associated with such changes that can result in intestinal inflammation and symptoms like weight loss, abdominal pain or diarrhea. This review summarizes our current knowledge on barrier dysfunction and claudin dysregulation in several intestinal diseases gastroenterologists are often faced with, like inflammatory bowel disease, microscopic colitis, celiac disease, irritable bowel syndrome, gallstones and infectious diseases like HIV enteropathy, Campylobacter jejuni and Clostridium perfringens infection.